Self-Concept Transformation on Senior Secondary School Students' Academic Achievement in Central Zone, Plateau State, Nigeria - Gwaison Panan Danladi; Shuaibu Saidu; Jacob, I. Otaha (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Economics is one of the popular subjects in the Senior Secondary School (SSS) curriculum, and it covers the fundamental aspects of human lives concerning scarcity of resources. Proper understanding of the basic concept will enable students to realize the benefit of the subject. This study examined the effects of the self-concept transformation package on senior secondary school student's academic achievement in the quantitative aspect of Economics in Central Zone, Plateau State, Nigeria. A quasi-experimental research design, the non-equivalent control- group design, was used for this study. The sample size consisted of 105 economics SS2 students from intact classes of the four sampled schools. There were 50 and 55 students in the experimental and control group, respectively. Multi-Stage Cluster sampling techniques were used for this study. The instruments used for data collection were the Multi-dimensional Self-Concept Scales (MSS) and Quantitative Economics Achievement Test (QEAT). Research questions were analyzed using descriptive statistics, while the t-test of independent sample and Analysis of Covariance (ANCOVA) was used to test the hypotheses. The statistical package for social sciences (SPSS) version 23 was used for the analysis. The results show that the self-concept transformation package positively and significantly affected students' self-concept and academic achievement in quantitative economics. The study recommended that the use of abusive words on students by Parents and guardians should be discouraged to strengthening their student's self-concept.